Rancang Bangun Aplikasi Penjualan Minyak Pada CV. Langgeng Jaya - Cahyono, Dwi; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
CV. LanggengJaya is a commercial enterprise engaged in the sale of bottled cooking oil with the brand "Iga Mas". The process of recording the price and the item code is manual. Such actions require recording process repeated thus inhibiting in the sales process receivable collection procedures. CV. Langgeng Jaya is a commercial enterprise engaged in the sale of bottled cooking oil with the brand "Iga Mas". The process of recording the price and the item code is manual. Such actions require recording process repeated thus inhibiting in the sales process receivable collection procedures. CV Langgeng Jaya also has disadvantages in terms of doing the collection of accounts receivable is due. Often there is a delay in collecting receivables to customers who have matured because of the difficulty in finding the data customer receivables. Based on these problems, it is built Design Edible Oil Sales Application at CV. Langgeng Jaya. This application consists of sales, accounts receivable reporting, sales reporting, calculating the cost of goods sold. The results showed that the Design Build Oil Sales Application at CV. Langgeng Jaya can be used to record, merekap sales data and generates nine major reports and the manager can use three invoices printed by part of the sales staff. There is a collection of accounts receivable reminder function that can be used by part of the sales staff to help deal with collection of accounts receivable. Lasting Jaya also has disadvantages in terms of doing the collection of accounts receivable is due. Often there is a delay in collecting receivables to customers who have matured because of the difficulty in finding the data customer receivables.Based on these problems, it is built Design Edible Oil Sales Application at CV. Langgeng Jaya. This application consists of sales, accounts receivable reporting, sales reporting, calculating the cost of goods sold. The results showed that the Design Build Oil Sales Application at CV. Langgeng Jaya can be used to record, merekap sales data and generates nine major reports and the manager can use three invoices printed by part of the sales staff. There is a collection of accounts receivable reminder function that can be used by part of the sales staff to help deal with collection of accounts receivable.